2021
DOI: 10.1115/1.4052894
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations Into the Local Behavior of Condensing R134a Flows in a Horizontal Pipe

Abstract: The local characteristics and behavior of condensing R134a flows in a horizontal pipe, at mass fluxes of 100, 200 and 400 kg/m2s, saturation temperature of 40 °C and mean vapor qualities of 0.25, 0.50 and 0.75, are investigated numerically. The local results demonstrate an increase in condensate film thickness from a particular angular position, which is influenced by the vapor quality of the flow, to the bottom of the pipe. The heat transfer coefficient decreases around the pipe circumference, that is from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Further research was performed by Juggurnath et al [41] on the characteristics of condensing flows of the refrigerant R134a in horizontal pipes. Considering mass fluxes of 100, 200 and 400 kg m −2 s −1 , a saturation temperature of 40°C, and mean vapour qualities of 0.25, 0.50 and 0.75, Juggurnath et al [41] found that the HTC decreased around the pipe circumference from the top of the pipe to the bottom.…”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research was performed by Juggurnath et al [41] on the characteristics of condensing flows of the refrigerant R134a in horizontal pipes. Considering mass fluxes of 100, 200 and 400 kg m −2 s −1 , a saturation temperature of 40°C, and mean vapour qualities of 0.25, 0.50 and 0.75, Juggurnath et al [41] found that the HTC decreased around the pipe circumference from the top of the pipe to the bottom.…”
Section: Computational Studiesmentioning
confidence: 99%
“…Further research was performed by Juggurnath et al [41] on the characteristics of condensing flows of the refrigerant R134a in horizontal pipes. Considering mass fluxes of 100, 200 and 400 kg m −2 s −1 , a saturation temperature of 40°C, and mean vapour qualities of 0.25, 0.50 and 0.75, Juggurnath et al [41] found that the HTC decreased around the pipe circumference from the top of the pipe to the bottom. The simulations performed by Juggurnath et al [41] found an asymmetrical velocity profile in the condensing R134a flow which the authors attributed to the stratified condensate layer present at the bottom of the pipes.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation